The loyal one - Gray, Shelley Shepard (Gray, Shelley Shepard. Walnut Creek series., 2019)
"The New York Times bestselling author of the Walnut Creek series crafts a moving and evocative novel of secrets, friendship, and second chances--perfect for fans of Kathleen Fuller and Beth Wiseman."--